Peran Komunikasi Horizontal dan Budaya Organisasi dalam Meningkatkan Kinerja Karyawan di Rocky Plaza Hotel Padang - Khofifah Winanda; Rita Destiwati (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to analyze the impact of horizontal communication and organizational culture on employee performance at Rocky Plaza Hotel Padang. In the hospitality industry, effective communication among employees and a supportive organizational culture are crucial to improving employee performance, which in turn affects service quality and guest satisfaction. This research uses a quantitative approach with a sample of 100 employees, selected through stratified random sampling. Data was collected via questionnaires and analyzed using linear regression and hypothesis testing. The results indicate that both horizontal communication (X1) and organizational culture (X2) have a positive and significant effect on employee performance (Y), with p-values of 0.000 for each, which is less than 0.05. These findings suggest that smooth communication among employees and the implementation of a supportive organizational culture can enhance both individual and overall organizational performance. The practical implication of this study is the importance of strengthening internal communication and fostering a positive organizational culture to improve productivity and service quality in the hospitality sector.